PERANCANGAN BUKU CERITA ANAK BERJUDUL THE LITTLE HERO AND HIS FRIEND QILIN - Vinna Vinna; Aprilia Kartini Streit (Jurnal Bahasa Rupa, 2022)
Indonesia has a lot of variety of dance arts. Starting from native to the results of acculturation.  Based on  questionnaires  conducted, some of people are less preserve the art of dance, especially Acculturation. The traditional dance is the most difficult art of dance. Some of traditional dances are the results from unpopular acculturation and exclusive . As the acculturation dances, One of  them is  qilin  dance. qilin dance comes from the culture of Hakka in Indonesia. This dance is only performed for a part of rituals.  The  reason is  qilin are a highly respected divine beast. which is very  disrespectful for devine beast to perfom dance as commercial. This research uses descriptive analysis method carried out as qualitative, by  collecting data from questionnaires. literature study, observation and documentary. With the results of the research that will produce the work of the qilin dance story book, this book will be published commercially to introduce qilin dance. From this research and create this children book, the author hopes people in indonesia will love more about  traditional dance, as the spirit of Bhineka Tunggal Ika.